Eulers - Backwards
1 view (last 30 days)
Show older comments
Hello everyone.
If I want to write Euler's (Backwards) y(tj)=y(tj-1)+h*f(tj,y(tj)) on the formula x=g(x).
then, what should 'g' and 'x' be?
My attempt so far:
y(tj)-y(tj-1)-h*f(tj,y(tj))=0 x=g(x)
Some help would be appreciated.
Regards Cillian
0 Comments
Answers (0)
See Also
Categories
Find more on Parallel Computing Fundamentals in Help Center and File Exchange
Community Treasure Hunt
Find the treasures in MATLAB Central and discover how the community can help you!
Start Hunting!